New Insights of the Zn(Ii)-Induced p2 × 4r Positive Allosteric Modulation: Role of Head Receptor Domain Ss2/Ss3, e160 and d170 - Garcia Huidobro-Toro, J; Peralta-Peralta, F (Multidisciplinary Digital Publishing Institute (MDPI), 2020)
P2 × 4R is allosterically modulated by Zn(II), and despite the efforts to understand the mechanism, there is not a consensus proposal; C132 is a critical amino acid for the Zn(II) modulation, and this residue is located in the receptor head domain, forming disulfide SS3. To ascertain the role of the SS2/SS3 microenvironment on the rP2 × 4R Zn(II)-induced allosteric modulation, we investigated the contribution of each individual SS2/SS3 cysteine plus carboxylic acid residues E118, E160, and D170, located in the immediate vicinity of the SS2/SS3 disulfide bonds. To this aim, we combined electrophysiological recordings with protein chemical alkylation using thiol reagents such as N-ethylmaleimide or iodoacetamide, and a mutation of key amino acid residues together with P2 × 4 receptor bioinformatics. P2 × 4R alkylation in the presence of the metal obliterated the allosteric modulation, a finding supported by the site-directed mutagenesis of C132 and C149 by a corresponding alanine. In addition, while E118Q was sensitive to Zn(II) modulation, the wild type receptor, mutants E160Q and D170N, were not, suggesting that these acid residues participate in the modulatory mechanism. Poisson–Boltzmann analysis indicated that the E160Q and D170N mutants showed a shift towards more positive electrostatic potential in the SS2/SS3 microenvironment. Present results highlight the role of C132 and C149 as putative Zn(II) ligands; in addition, we infer that acid residues E160 and D170 play a role attracting Zn(II) to the head receptor domain. © 2020 by the authors. Licensee MDPI, Basel, Switzerland.